2016
DOI: 10.1111/jvp.12368
|View full text |Cite
|
Sign up to set email alerts
|

Repeated oral administration of a cathepsin K inhibitor significantly suppresses bone resorption in exercising horses with evidence of increased bone formation and maintained bone turnover

Abstract: Our investigations evaluated the effect of VEL-0230, a highly specific irreversible inhibitor of cathepsin K (CatK). The objectives of our study were to determine whether repeated dosing of a CatK inhibitor (CatKI) produced a desired inhibition of the bone resorption biomarker (CTX-1), and document the effect of repeated dosing on bone homeostasis, structure, and dynamics of bone resorption and formation in horses. Twelve young exercising horses were randomized in a prospective, controlled clinical trial and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
1
9
0
3
Order By: Relevance
“…Therefore, it was hypothesized that if there were a systemic effect of tiludronate or clodronate administration in the horse at the routine clinical dose administered, it would have been detected in the current study. In addition, a recent study evaluating the effect of the bone resorption inhibitor cathepsin K, which does not fully prevent osteoclastic resorption as bisphosphonates have been shown to do [ 31 ], was performed with groups of 6 horses, with significant differences found [ 32 ]. Therefore, we conclude that the lack of changes identified in the current study, especially related to the re-biopsy results and effects on a model of bone healing, are truly reflective of an overall lack of influence of these drugs on bone remodeling kinetics in the horse.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was hypothesized that if there were a systemic effect of tiludronate or clodronate administration in the horse at the routine clinical dose administered, it would have been detected in the current study. In addition, a recent study evaluating the effect of the bone resorption inhibitor cathepsin K, which does not fully prevent osteoclastic resorption as bisphosphonates have been shown to do [ 31 ], was performed with groups of 6 horses, with significant differences found [ 32 ]. Therefore, we conclude that the lack of changes identified in the current study, especially related to the re-biopsy results and effects on a model of bone healing, are truly reflective of an overall lack of influence of these drugs on bone remodeling kinetics in the horse.…”
Section: Discussionmentioning
confidence: 99%
“…VEL-0230 was used in a mass concentration of 0.3 μg/ml of culture media to achieve the lowest molar concentration of 1μM. However, the maximum plasma concentration of VEL-0230 did not exceed 0.1μg/ml, achieved using an oral dose regimen of 4mg/kg of body weight q7 days in healthy exercising horses, and by which resulted in a marked decline in bone resorption without altering the number of osteoclasts as confirmed by TRAP staining of bone biopsies and subsequent analysis [8,10] .…”
Section: Discussionmentioning
confidence: 98%
“…Biopsy samples were collected from six of the horses from the Tuber coxae (TC), a non-weight-bearing bone, and the proximal phalanx (P1), a weight-bearing bone, as previously described [10] . Horses were randomly assigned to left or right TC and forelimb P1.…”
Section: Bone Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…At present, research results demonstrated the strong antiresorptive activity and high selectivity of some inhibitors 10 . Furthermore, several Cat K inhibitors under preclinical or clinical investigation for indications such as bone metastases, rheumatoid arthritis or osteoporosis have made optimistic and positive progresses 11–13 .…”
Section: Introductionmentioning
confidence: 99%